Studi Eksploratif Terhadap Temuan Pemeriksaan BPK RI Atas Sistem Pengendalian Internal Kabupaten/Kota di Propinsi Sumatera Barat - Vita Fitria Sari; Marina Octaviani; Yeni Lisdawati (Universitas Negeri Padang, 2018)
Effectiveness of internal control system is one of criteria in obtaining audit opinion of local government financial statement. The problems arises by looking at repeated findings on audit reports in effectiveness of internal control which means there is no follow up of audit findings by local government. This research aims to identify what accounts amd problems mostly faced in local government internal control system and detect repeated finding that occurred related to implementation local government of internal control systems. The object of this study are audit reports of local government launched by Badan Pemeriksa Keuangan for 10 regencies/ cities in West Sumatera Province during 2014-2016. This research classified by qualitative research by using content analysis. The results of this study found that current assets and revenue are most often appears in audit findings related to weakness of internal control systems. Problems related to audit findings on internal control systems mostly related with control activities and environment’s control. This study also found that there are still recurring findings during 2014-1026 related to internal control system which means lack of follow up of audit findings.Keywords: audit findings, audit reports, content analysis, internal control systems